Application of a computer sound card for measurement of mechanical vibrations - Barros, Everaldo De; Souto, Carlos D'andrade; Camargo, Leandro Ribeiro De; Mathias, Mauro Hugo [UNESP] (Sociedade Brasileira de Física, 2015)
This paper presents a data acquisition and analysis system based on a computer sound card for measuring and processing random vibration signals. This system turns the computer into a two-channel measurement instrument which provides sample rate, simultaneous sampling, frequency range, filters and others essential capabilities required to perform random vibrations measurements. An easy-to-use software was developed for vibration monitoring and analysis, including facilities for data recording, digital signal processing and real time spectrum analyzer. Since the tasks of vibration data acquisition frequently require expensive hardware and software, this versatile system provides students a very accurate and inexpensive solution for experimental studying mechanical vibrations.

Este trabalho apresenta um sistema de aquisição e análise de dados baseado em uma placa de som de computador para a medição e processamento de sinais de vibração. Este sistema transforma o computador em um instrumento de medição de dois canais, disponibilizando taxa de amostragem, amostragem simultânea, faixa de freqüência, filtros e outros recursos essenciais necessários para realizar medições de vibrações aleatórias. Um software com facilidades de utilização foi desenvolvido para o monitoramento e análise de vibrações, incluindo recursos para gravação de dados, processamento dos sinais e analisador de espectro em tempo real. Uma vez que as tarefas de aquisição de dados de vibração geralmente requerem hardware e software de custo elevado, este sistema versátil oferece aos estudantes uma solução precisa e barata para o estudo experimental de vibrações mecânicas.
(Aplicação de uma placa de som de computador para medição de vibrações mecânicas)
Keywords: data acquisition system; vibrations; computer sound card; sistema de aquisição de dados; vibrações; placa de som de computador